(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2015)
Depleted uranium (U-238) decays very slowly, with its half-life same as the age of the earth. This means that it is virtually indestructible. Although it is barely radioactive, less than many other isotopes in rocks and sand, it does generate energy (in form of kinetic heat) of 0, l watt /ton which is enough to warm the Earth’s crust. Uranium- 238 emits alpha particles which penetrates the material more difficult compared with other forms of radiation and also weak gamma rays. As long as it remains outside the body, the uranium poses a small health risk (caused mainly by gamma rays). If it is inhaled or added to the digestive system, its radiation carries an increased risk of lung cancer and bone cancer. Uranium in high concentrations is also chemically toxic and can cause damage to internal organs, especially the kidneys. Animal studies alert that uranium may affect reproduction, the developing fetus, and may increase the risk of leukemia and of the soft tissue cancer. DU at the present is a subject of numerous discussions on its use and storage. Since the existence of regulations and prohibitions, their amplification by creation of numerous commissions, since initiated or proposed measures of protection against the harmful effects of DU Js production facilities and test ranges in the past as well as the present, and since (not so) recent restrictions on testing of DU ammunition, it is evident that governments and military authorities are aware that the expanded use of DU is harmful both to people and the environment. They are also aware of the fact that the DU radioactivity is sufficient to condition the removal of contaminated facilities, including country soil from DU production areas and testing polygons. Because of the general anxiety by which many people look upon this problem, the radiological and the toxicological characteristics of DU should take own place in the training and education of the armed forces and civilians, as a way of reducement of any risk possibilities. Because DU ammunition is available to many nations, it is likely to expect contamination being spread to all future combat areas. Hence, the knowledge, the expertise and the equipment for prevention or mitigation of exposure must be equally distributed.